Transdermal Optical Imaging Reveal Basal Stress via Heart Rate Variability Analysis: A Novel Methodology Comparable to Electrocardiography - Wei, Jing; Luo, Hong; Wu, Si J.; Zheng, Paul P.; Fu, Genyue; Lee, Kang (Frontiers in Psychology, 2018)
The present study examined the validity of a novel physiological measurement technology called transdermal optical imaging (TOI) technology at assessing basal stress. This technology conveniently, contactlessly, and remotely measures facial blood flow changes using a conventional digital video camera. We compared data from TOI against the pulse data collected from the FDA approved BIOPAC system. One hundred thirty-six healthy adults participated in the study. We found that TOI measurements of heart rate and heart rate variability, which reflects basal stress, corresponded strongly to those obtained from BIOPAC. These findings indicate that transdermal optical imaging technology is a viable method to monitor heart rate and heart rate variability not only accurately but also conveniently, contactlessly, and remotely. Further, measures of heart rate variability obtained via transdermal optical imaging serves as a valid index of basal stress. Potential applications of this technology in psychological research and other fields are discussed.